Estimating the Proportion of Essential Tremor and Parkinson's Disease Patients Undergoing Deep Brain Stimulation Surgery: Five‐Year Data From Columbia University Medical Center (2009–2014). Issue 4 (25th July 2015) - Kestenbaum, Meir; Ford, Blair; Louis, Elan D.
Abstract: Objective: The aim of this study was to estimate, at a tertiary referral center, the proportion of essential tremor (ET) and Parkinson's disease (PD) patients who underwent DBS surgery. Background: DBS surgery is an important treatment for ET and PD. Surprisingly, there are no published data on the precise proportion of such patients who are referred for this procedure. Methods: Using the computerized billing database at the Center for Parkinson's Disease and Other Movement Disorders, Columbia University Medical Center, we searched for patients who received the diagnostic codes 333.1 (tremor) and 332.0 (PD) and who were followed by a doctor at the center during the 5‐year period from 2009 to 2014. The number of patients who underwent DBS surgery for these diagnoses during this time period was also determined. Results: Seventy‐seven patients with these diagnoses (52 PD, 14 ET, and 11 ET + PD) who were followed at the center underwent DBS surgery during this time period. The proportion of ET patients who underwent DBS surgery was 2.90% (95% confidence interval [CI]: 1.78–4.02), and for PD this was 1.38% (95% CI: 1.04–1.72). The difference was significant ( P < 0.001). Conclusions: At a tertiary‐referral center, 1 in 34 ET patients and 1 in 72 PD patients underwent DBS surgery. Similar studies from other major centers would be of additional value. These data are likely to have utility when planning health care services for patients with these diagnoses.